2021
DOI: 10.3390/f12060778
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Polyploid Varieties of Acacia: Reproductive and Early Growth Characteristics of the Allotetraploid Hybrid (Acacia mangium × A. auriculiformis) in Comparison with Diploid Progenitors

Abstract: Diploid clones of the hybrid acacia (Acacia mangium × A. auriculiformis) are widely planted in Vietnam because of their high productivity, adaptability, and commercial wood yields. Polyploid breeding offers possibilities for further enhancing hybrid vigor and generating new high value genotypes. In a field trial, we compared three diploid hybrid clones with their respective colchicine-induced tetraploid lines. Flowering and seed production of each cytotype were observed and open pollinated seed collected for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…The tetraploid A. mangium tree has a gigantism effect and showed 21% coarser and thicker bark, 20% thicker polyads, 28% longer wood fiber, 17% thicker leaves, 12% wider leaves, and longer stomata (24.3 µm) compared to the diploid tree (Griffin, 2014). Likewise, the tetraploid tree produced a larger seed and a higher flowering capacity than the diploid tree (Le et al, 2021). Additionally, da Silva Souza et al (2021) reported that polyploid Eucalyptus clones derived from the crosses of E. grandis × E. urophylla produced a longer and thicker cell wall of wood fibers than the diploids, thus increasing the fiber strength of the paper products.…”
Section: Accordingmentioning
confidence: 99%
See 1 more Smart Citation
“…The tetraploid A. mangium tree has a gigantism effect and showed 21% coarser and thicker bark, 20% thicker polyads, 28% longer wood fiber, 17% thicker leaves, 12% wider leaves, and longer stomata (24.3 µm) compared to the diploid tree (Griffin, 2014). Likewise, the tetraploid tree produced a larger seed and a higher flowering capacity than the diploid tree (Le et al, 2021). Additionally, da Silva Souza et al (2021) reported that polyploid Eucalyptus clones derived from the crosses of E. grandis × E. urophylla produced a longer and thicker cell wall of wood fibers than the diploids, thus increasing the fiber strength of the paper products.…”
Section: Accordingmentioning
confidence: 99%
“…Various studies on the use of antimitotic agents for polyploidy induction have been done on many forestry plants. The purpose of those studies was to improve the quality and quantity of plants and plant products, such as Eucalyptus grandis (Silva, Carvalho, & Clarindo, 2019), E. dunnii (Castillo, Lopez, Tavares, Santinaque, & Dalla Rizza, 2020), Aquilaria malaccensis (Siti-Suhaila et al, 2020), Acacia mangium (Griffin, 2014;Viet et al, 2020;Le et al, 2021), and T. grandis (Nugraha, 2012;Ridwan, Handayani, Riastiwi, & Witjaksono, 2018).…”
Section: Accordingmentioning
confidence: 99%
“…Polyploid trees, Melia volkensii among others, may be of interest for forest plantations for providing better wood quality and performance under stress conditions compared to diploid trees [33,34]. Tetraploid Acacia mangium clones that were eight years old had pulp with longer and wider fibers, higher mass, porosity, and tear strength than diploid Acacia mangium clones that were the same age [35].…”
Section: Introductionmentioning
confidence: 99%
“…While appealing as a model, it is, however, likely to be at most transient, since even small amounts of non-preferential recombination can rapidly homogenize the genome (Muramatsu 1990 ; Sybenga 1996 ; Meirmans and Van Tienderen 2013 ), generating chimeric chromosomes whose recombination partner choice will depend on where recombination events are located along the chromosome. Thus, it is perhaps unsurprising that the only known examples of this kind of intermediate-preference system are recent hybrids, including interspecies hybrids in Rorippa , sugar cane and Acacia (Jannoo et al 2004 ; Stift et al 2008 ; Xie et al 2015 ; Le et al 2021 ). However, even if they are likely evolutionarily ephemeral, such systems can teach us interesting things about the effects of hybridization in polyploid systems, and how higher ploidy levels and/or complex auto-allopolyploids can evolve.…”
mentioning
confidence: 99%